KORELASI ASPEK KOGNITIF TERHADAP TINGKAT KEPATUHAN PENGOBATAN TUBERKULOSIS - Anshari, Muhammad; Haluruk, John Davison; Aipipidely, Diana; Setyobudi, Agus (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2025)
Abstract: Tuberculosis (TB) remains one of the most significant public health issues globally. During treatment, the length of the treatment period often causes patients to feel bored. The aim of this study was to determine the correlation between cognitive aspects and the level of adherence to tuberculosis treatment. The research design used in this study was cross-sectional. The study was conducted at the Pacar Keling Health Center in September 2024. The study population consisted of all pulmonary TB patients at the Pacar Keling Health Center, totaling 37 patients. The sample size was 34 patients. The sampling technique used in this study was simple random sampling. Data analysis was performed using univariate and bivariate methods. The results of the study showed a relationship between the level of knowledge (p-value: 0.000) and motivation (p-value: 0.004) with tuberculosis treatment adherence. It is recommended that the health center implement health promotion activities based on self-care to address patient non-adherence in improving adherence to the treatment program and enhancing the health status of pulmonary tuberculosis patients.Keywords: Compliance, Motivation, Knowledge.